Situación Del Emprendimiento Y Sus Alcances En El Ecuador - Borja, René Mesías Villacrés (European Scientific Journal, ESJ, 2017)
Entrepreneurship, over the last 20 years, has been of vital importance throughout the world. Also, many educational institutions have been concerned with creating careers in these areas, especially when a serious research such as the GEM was followed due to several years of entrepreneurship activity. Many countries have sought to promote the entrepreneurial spirit through actions aimed at providing training, incentive for business start-ups, and financing. This, however, is based on the fact that entrepreneurship is considered as the motor of a country's development, especially in times of crisis. In Ecuador, entrepreneurship plays an important role in the generation of employment, investment, production, consumption, and income for the state. These roles are attributable to the fact that Ecuador is a country where entrepreneurship is generated by opportunity and necessity. The present research is of a bibliographical character since it uses documents which were based on statistical information and other sources in which the situation of the enterprise was analyzed. Analytical method was used to obtain real information based on observation and analysis. It is also based on the inductive part of a particular situation. In general, it derives knowledge that are proposed. The deductive method starts from general data and through logical reasoning, it comes to a particular consideration and conclusion. The objective of the research is to analyze the beginning of entrepreneurship in the current situation in Ecuador.